Professional Development Strategies and Recommendations for High School Teachers to Teach Computer Science Online. Issue 2 (3rd April 2023) - Martin, Florence; Shanley, Nicole; Hite, Nicole; Pugalee, David; Perez-Quinones, Manuel; Ahlgrim-Delzell, Lynn; Hart, Ellen
Abstract: Based on a current Research to Practice Partnership (RPP) between a southeastern public university and a state virtual public school in the United States, ten high school teachers from a virtual school who teach Computer Science (CS) online participated in a summer workshop to collaborate through a participatory action research project regarding design, facilitation, and evaluation strategies to be included in effective professional development. The questions were posed through an online collaborative Jamboard during the summer workshop. The teacher posts were qualitatively analyzed to identify common themes. Recommendations for professional development on design included CS content, how to teach CS, and CS tools and activities. For facilitation, they recommended resources for supplemental instruction and feedback tools for providing feedback in various modalities and a tool repository. For assessment, they recommended content knowledge assessments, including lab assignments, single and pair programming, and coding assessments. Overall recommendations for a professional development course to teach CS online were also offered.